ORGANIZATION OF INNOVATIVE ACTIVITIES OF TEACHERS OF MULTIDISCIPLINARY PRESCHOOL EDUCATION IN AN EDUCATIONAL CLUSTER (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
This article talks about the organization of innovative activities of teachers of multidisciplinary preschool education in an educational cluster.